Corporate Strategy and Performance of Kenyan Companies - Awino, Zachary; Machuki, Vincent; Ogaga, Bruce J (Archives of Business Research, 2017)
The study examines the effect of corporate strategy on organizational performance. A structured questionnaire was used to collect data from 46 companies listed on the Nairobi Securities Exchange. Descriptive and inferential statistics were used to analyze the data. The study findings reveal that corporate strategy has significant effect on organizational performance. A theoretical and empirical implication of the study illustrate that the stakeholder theory is fully supported. Methodological implication shows that the validity and reliability tests carried out on the data collection instruments confirm that the instrument is sufficient to collect data from respondents. The researchers recommend future research on the individual corporate strategy constructs tested against the raw score of each of the seven performance indicators of Kenya’s publicly quoted companies.